STD, HIV and Aids scientific publications: description of bioethical procedures in the instructions for the authors and in selected papers - Calvetti, Prisla U.; Harzheim, Erno; Viana, José Lândio; Germany, Cíntia; Ramos, Mauro C. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: Bioethics in research with human participants has permitted to address ethical aspects of the health field. STD, HIV and AIDSresearch is currently amongst the more productive research fields. Objective: To review scientific journals and selected papers in order to evaluatethe presence of ethical requirements and description of ethical procedures. Methods: Bibliographic review of an electronic database (SciELO) usingthe key words STD, HIV and AIDS, identifying the journals that have published papers in the field from 2001 to the present date. Available journal swere reviewed, and the sections of instructions for authors and methodology of selected papers were evaluated. Results: Of the 33 journals reviewed,67% (22) have mentioned the requirement of getting an approval of the research project by an ethical review board and 39% of the articles have men-tioned this aspect. Ethical principles of confidenciality, privacy and autonomy were mentioned in 15% of the evaluated papers, and in 51% of theminformed consent had reference of the informed consent. Conclusion: Mentioning ethical procedures has not have the needed consideration byresearchers in the field of STD, HIV and AIDS, although it does not necessarily mean that ethical procedures have not been implemented. In the presence of significant scientific and technological achievements, it is necessary that researchers have equivalent concern on bioethics and on responsible behavior in research, including in mentioning the bioethics procedures implemented in their research projects.